Disease Activity and Tendency to Relapse in ANCA-Associated Vasculitis Are Reflected in Neutrophil and Intermediate Monocyte Frequencies - Sofia Smargianaki; Evelina Elmér; Sandra Lilliebladh; Sophie Ohlsson; Åsa Pettersson; Thomas Hellmark; Åsa CM Johansson (Journal of Immunology Research)
Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a group of autoimmune diseases with inflammation affecting small blood vessels and includes granulomatosis with polyangiitis (GPA) and microscopic polyangiitis (MPA). In this study, we investigated granulocyte and monocyte subsets in a large cohort of AAV patients with emphasis on disease activity and tendency to relapse. A cohort of 105 patients with GPA or MPA and 126 healthy controls (HCs) were included. Clinical and laboratory data were collected for all patients, including disease activity, tendency to relapse, and pharmacological treatment. Using flow cytometry, circulating eosinophils, basophils, neutrophils, and monocytes were assessed. The monocytes were subdivided into classical (CD14++CD16−), intermediate (CD14++CD16+), and nonclassical (CD14−CD16+) monocytes. Mature (CD16high) or newly released (CD16dim) neutrophils were defined, as well as the frequency of CD177+ neutrophils. AAV patients displayed increased frequencies of intermediate monocytes, mature and newly released neutrophils, and an expanded population of CD177+ neutrophils compared to HC. MPA patients differed from GPA patients in terms of lower frequency of classical monocytes. No differences in cell frequencies regarding ANCA phenotype were observed. Paired data from 23 patients demonstrated that active disease was associated with an increased frequency of mature neutrophils and a decreased frequency of monocytes, in particular intermediate monocytes. Moreover, GPA patients with a tendency to relapse displayed an increased frequency of mature neutrophils with increased expression of CD177+. Relapsing MPA patients, on the other hand, showed decreased frequency of intermediate monocytes. Finally, rituximab treatment was associated with increased frequencies of classical and intermediate monocytes. In conclusion, AAV patients exhibit a skewing of different neutrophil and monocyte subpopulations that are associated with disease subtypes, disease activity, rituximab treatment, and propensity to relapse. These changes may contribute to the inflammatory process and could potentially be used as biomarkers for relapse prediction.